Difference Between BMI At Admission and Discharge and NIHSS at Admission and Discharge In Iscemic Stroke Patients at Dr.Kariadi Horpital - Fauziah, Annisa; Subagio, Hertanto Wahyu; Nugrohowati, Annta Kern; SS, Darmono; Probosari, Enny (RSUP Dr. Kariadi, 2023)
BACKGROUND : Hospitalized patients are at risk for malnutrition. Decreased BMI (Body Mass Index) in stroke patients is negatively correlated with patient outcomes. Studies on differences in BMI and NIHSS (National Institutes of Health Stroke Scale) at admission and discharge in stroke patients have not been conducted in Indonesia. OBJECTIVE: To describe the difference between BMI and NIHSS at admission and discharge in ischemic stroke patients at Dr. Kariadi hospital METHOD : An observational study on 49 hospitalized ischemic stroke patients at the Stroke Unit of dr. Kariadi hospital. Outcomes were measured using the National Institutes of Stroke Scale (NIHSS). Data was collected from the patient's medical record and analyzed using Paired Sample t Test. RESULT : There was no significant difference between BMI at admission and discharge (p = 0.161). There was a significant difference between the NIHSS at the time of admission and at the time of discharge (p= 0.014). CONCLUSION : There is no significant difference between BMI at admission and discharge. There is functional improvement in ischemic stroke patients during treatment